The Effect of Reading the Holy Al-Quran on Stress Levels Among Patients with Hypertension - Sukron, Sukron; Sari, Indah; Aristoteles, Aristoteles; Wahyudi, Joko Tri; Phutthikhamin, Nichapatr; Rahmadhani, Wulan; Ameilia, Ade Dwi (Media Publikasi Cendekia Indonesia, 2025)
The impact of psychological conditions faced by hypertension patients is stress. This can disrupt physical activity and make the condition more serious if nursing intervention is not provided. Reading the holy Al-Qur'an is one alternative that can reduce stress levels. It is can reduce stress hormones and increase feelings of relaxation and improve body chemistry so that it can reduce blood pressure and stress levels. The study aimed to determine the effect of reading the Al-Qur'an on stress levels in hypertension patients. This study uses quantitative research with a pre-experiment research a one group pre-posttest design. The sampling technique uses purposive sampling, namely respondents with hypertension as many as 63 respondents. The intervention of reading the Al-Qur’an by choosing a surah that the patient is able to do with a moderate tone of voice. The instrument uses the Perceived Stress Scale (PSS). The results of the study showed that, the average score of stress levels before the intervention for the low category was a mean of 21.56 (SD = 0.72), while the moderate category was the mean score of 38.17 (SD = 4.20). Then the mean score of stress levels after the intervention for the low category was the mean score of 19.10 (SD = 2.87), and the moderate category was the mean score of 25.71 (SD = 3.45). The Wilcoxon test found that the p-value was 0.001 (p <0.05) which means that there is an effect of reading the Qur'an on stress levels in hypertensive patients. It is hoped that to the Muhammadiyah Hospital Palembang can implement the intervention of reading the Al-Qur’an for patients with hypertension which is useful for reducing the stress level of patients.